2019
DOI: 10.33223/epj/109338
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of energy production and consumption in European Union countries

Abstract: The aim of the research is to assess and discuss the diversity of energy production and consumption in European Union countries. The time scope covers the years 2007 and 2016. The diversity of EU countries was examined using the cluster analysis. The following diagnostic features were adopted for the analysis: energy dependency rate (in %), gross inland consumption of energy per 10,000 inhabitants (toe/10,000 inhabitants), primary production of energy (all products) per 10,000 inhabitants (toe/10,000 inhabitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the literature, research was conducted on the grouping of European Union countries, inter alia, in terms of the structure of energy production from renewable source [79] and also in terms of the level of production and consumption of electricity [80]. The results of comparative analyzes in the above-mentioned perspectives show different results of grouping countries due to different diagnostic variables adopted for multivariate analysis and different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, research was conducted on the grouping of European Union countries, inter alia, in terms of the structure of energy production from renewable source [79] and also in terms of the level of production and consumption of electricity [80]. The results of comparative analyzes in the above-mentioned perspectives show different results of grouping countries due to different diagnostic variables adopted for multivariate analysis and different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Global energy demand is growing worldwide in both developing and developed countries [68,69]. Energy companies are facing new challenges as the growing demand for energy cannot be supplied predominantly from fossil energy sources as today due to the progressive climate change.…”
Section: Directions Of Strategic Development Of the Energy Market In Poland Versus Expectations In Terms Of Employee Competenciesmentioning
confidence: 99%
“…The study showed that the formation of modern approaches to energy management of a business organization took place within the evolutionary process of forming an appropriate system of scientific knowledge. It ranged from theoretical views on the economics of rational consumption of natural resources (Kudlaj and Seliverstova 2013;Janiszewska 2019;Lior 2008) to recogni-zing energy efficiency as an important prerequisite for the competitiveness of individual business organizations (Gökgöz and Güvercin 2018), and ensuring the stability of the state's economy (Deny`syuk et al eds. 2016;Ossowska and Janiszewska 2020).…”
Section: The Theoretical Bases Of the Business Organization Energy Samentioning
confidence: 99%